Penjadwalan Dinas terhadap Kepuasan Kerja Perawat di Rumah Sakit Y Jakarta - Rizany, Ichsan; Hariyati, Rr Tutik Sri; Afiyanti, Efi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Nurses work professionally in hospitals to provide nursing services so that patients feel satisfied with thework ofnurses. But nurse job satisfaction in hospitals in Indonesia is still low. Several factors most influencedlow nurse job satisfaction. One of them is nurse service scheduling. Nursing scheduling is the arrangementand allocation of time available to carry out tasks from the work of nurses. The purpose of this study was todetermine the relationship between nursing scheduling with patient satisfaction at Y Hospital Jakarta. Thisstudy method was cross-sectional. The number ofsamples was 32 nurses (n = 32) through a stratified randomsampling technique. The study was conducted at Y Hospital Jakarta. Inclusion criteria included nurse,worked at least 1 year in ward, and were willing to become respondents. Analyzed of data used Pearsoncorrelation test. The results showed that the average nurse job satisfaction was 73, while the nurse'sscheduling was 90. 29. These results indicated that nurse satisfaction was still below the minimum servicestandard (SPM). This result also showed that there was a significant relationship between nursing schedulingand nurse satisfaction (p = 0.040; r = 0.349). The conclusion of this study was that there was a significantrelationship between nursing scheduling and nurse satisfaction at Y Hospital. Recommendations were givento the Head of the room to be fair in making the official schedule. Hospital managers also are expected toimprove nurse satisfaction by managing to nurse scheduling properly.